Pengaruh Pandemi COVID-19 Terhadap Pelaksanaan Tradisi Ngabuburit pada Mahasiswa di Kota Bandung - Isaac Bernadus; Nadien Proton; Syifa Hanifah (UNIVERSITAS RAHARJA, 2021)
Ngabuburit in Indonesian society is a tradition that has been inherited from past generations. The practice of Ngabuburit however has been hampered due to the COVID-19 pandemic. To prevent the spread of COVID-19 virus, the government issued several regulations. These regulations make it more difficult for the community to practice Ngabuburit. This study was conducted to find out the effects of the COVID-19 pandemic on Ngabuburit, the interest of university students in Bandung in practicing Ngabuburit, and to find out the best method to practise Ngabuburit tradition amidst the COVID-19 pandemic according to university students. Methods used in this study are literature study and primary data collection through questionnaires. The research result indicates that COVID-19 pandemic has reduced the intensity of Ngabuburit in Bandung. The obstruction of Ngabuburit practices correlates with the decline in the average level of happiness of students in Bandung. Even though the practice of Ngabuburit tradition is hampered, said tradition still can be carried out through online methods, namely methods that rely on internet technology so that there is no need to meet face to face. Hopefully this research will be useful for those who wish to practise Ngabuburit tradition amidst the COVID-19 pandemic.